2018
DOI: 10.1007/s10726-018-9561-2
|View full text |Cite
|
Sign up to set email alerts
|

The Price of Team Spirit for Sensemaking Through Task Discourse in Innovation Teams

Abstract: Despite interest in innovation teams, we have only limited insights into how team members make sense of innovation teams' inherent ambiguity. By referring to the sensemaking literature and to the research on task discourse, this study introduces task discourse as a valuable sensemaking mechanism in innovation teams. We argue that team creativity and feasibility testing increase the need for task discourse, which, in turn, improves team performance. We further consider ambivalent effects of team spirit. On one … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(22 citation statements)
references
References 87 publications
(107 reference statements)
0
20
1
Order By: Relevance
“…In contrast to these findings, Ratzmann et al (2018) found that the direct impact of TC on a generalized measure of team performance is not statistically significant, but that the indirect impact of TC on team performance through task discourse is significantly positive. Ratzmann et al (2018) propose that task discourse functions as a mediator between TC and team performance by functioning as a mechanism for team members to challenge the innovation potential of ideas and to refine their ideas. Bonner et al (2002) took a different approach, positioning TC (operationalized as product innovativeness) as a moderator of project performance.…”
Section: Findings On the Impact Of Team Creativity On Performance Outcomescontrasting
confidence: 76%
See 2 more Smart Citations
“…In contrast to these findings, Ratzmann et al (2018) found that the direct impact of TC on a generalized measure of team performance is not statistically significant, but that the indirect impact of TC on team performance through task discourse is significantly positive. Ratzmann et al (2018) propose that task discourse functions as a mediator between TC and team performance by functioning as a mechanism for team members to challenge the innovation potential of ideas and to refine their ideas. Bonner et al (2002) took a different approach, positioning TC (operationalized as product innovativeness) as a moderator of project performance.…”
Section: Findings On the Impact Of Team Creativity On Performance Outcomescontrasting
confidence: 76%
“…2.6.1 The impact of team creativity on communication. As mentioned previously, Ratzmann et al (2018) positioned task discourse as a mediator between TC and performance and found that TC had a significant indirect positive impact on performance through task discourse. This finding was discussed more thoroughly in Section 2.4.1.…”
Section: The Impact Of Team Creativity On Processesmentioning
confidence: 79%
See 1 more Smart Citation
“…Especially, the open and autonomous interaction among users of coworking spaces brings internal contradictions on the level of the users. Actors might start with some informal conversations, then extend this to information and knowledge change, helping each other, working for each other and then moving into joint work-, team-, project-, and firm-relationship Ratzmann et al 2018). Yet some status and power relations might come into play (Clauss and Bouncken 2019).…”
Section: Mutability Internal Contradictions and Multiplicity Of Rulementioning
confidence: 99%
“…Following the example of Mainemelis (2010) and Ratzmann et al (2018), the final restriction for inclusion in the sample was that the team must feel constrained for resources. The need for bricolage arises when the resources the organization provides for the elaboration of new ideas are not sufficient.…”
Section: Sample and Data Collectionmentioning
confidence: 99%